1998
DOI: 10.1258/1357633981931867
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of telemedicine

Abstract: There are a number of different costs associated with the development and operation of telemedicine services. A model is proposed in order to assist in strengthening the evidence base for telemedicine. It includes the following components: project establishment costs; equipment costs; maintenance costs; communication costs; staffing costs. All need to be considered in arriving at an annual cost figure for operating a telemedicine service. The inclusion of all these costs, prepared in the standard manner outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 6 publications
(8 reference statements)
0
26
0
Order By: Relevance
“…Some experiences showed that, if usability issues are not well addressed, even well-motivated patients may not use such systems in their routine self-monitoring. 25 Finally, the use of computerized systems may have an economic impact, for example, by increasing personnel costs, 26 due to the necessity of providing users with assistance in case of system breakdowns or for simple help requests. On the other hand, IT solutions, and in particular telecommunication systems, may reduce the number of periodical control visits in comparison to normal clinical practice, and in some situations may avoid hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiences showed that, if usability issues are not well addressed, even well-motivated patients may not use such systems in their routine self-monitoring. 25 Finally, the use of computerized systems may have an economic impact, for example, by increasing personnel costs, 26 due to the necessity of providing users with assistance in case of system breakdowns or for simple help requests. On the other hand, IT solutions, and in particular telecommunication systems, may reduce the number of periodical control visits in comparison to normal clinical practice, and in some situations may avoid hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…14,22 The CEA for the TelemedicineIslands project was done by Bracale et al, 30 rural telemedicine collaborative care intervention for depression by Pyne et al, 14 cognitive behavioral therapy for bulimia nervosa by Crow et al, 15 and telemedicine services for the delivery of outpatient pulmonary care for a rural population by Agha et al 22 Many articles are reviews of cost-effectiveness studies of telemedicine systems and the importance of performing a good analysis. [32][33][34][35][36][37][38] All reviews are from 1998 to 2002.…”
Section: Review Of Cost-utility and Cost-effectiveness Studiesmentioning
confidence: 99%
“…[25][26][27] We calculated costs for ATSM only, as there were no additional costs associated with usual care (ATSM was an adjunct to this care), and because use of health care services did not differ between the 2 groups. Intervention costs included nurse care manager training; development of ATSM messages; translation and recording of messages in 3 languages; programming setup costs for ATSM; patient recruitment and follow-up time; fi xed monthly ATSM maintenance; costs associated with outgoing weekly ATSM calls; and direct nurse telephone care management with patients.…”
Section: Cost Measurementsmentioning
confidence: 99%